2022
DOI: 10.1186/s13007-022-00900-3
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for Chenopodium quinoa pollen germination

Abstract: Background Quinoa is an increasingly popular seed crop frequently studied for its tolerance to various abiotic stresses as well as its susceptibility to heat. Estimations of quinoa pollen viability through staining methods have resulted in conflicting results. A more effective alternative to stains is to estimate pollen viability through in vitro germination. Here we report a method for in vitro quinoa pollen germination that could be used to understand the impact of various stresses on quinoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Each type is differentiated by changes in size and circularity, allowing the software to easily distinguish and count between the elongated shapes of the viable pollen (type 1 and 2) from the rounded shapes of non-viable pollen (type 3 and 4) (Webber & Bonnet-Masimbert 1993). This represents an advantage over what is observed in most species, where pollen tube elongation implies a challenge for the creation of a reproducible macro, since under in vitro conditions individual tubes grow at different speeds and can take irregular shapes (Webber & Painter 1996); these irregularities may necessitate extensive manual corrections during analysis (Castillo et al 2022). This limitation may be the main reason for the lack of general macros to quantify germination in other species; however, the results presented here may be applicable to larch (Larix) pollen, which also follows a pre-germinative pattern similar to Pseudotsuga, as well as for other members of the genus (Ho & Rouse 1970, Takaso & Owens 1994, von Aderkas et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each type is differentiated by changes in size and circularity, allowing the software to easily distinguish and count between the elongated shapes of the viable pollen (type 1 and 2) from the rounded shapes of non-viable pollen (type 3 and 4) (Webber & Bonnet-Masimbert 1993). This represents an advantage over what is observed in most species, where pollen tube elongation implies a challenge for the creation of a reproducible macro, since under in vitro conditions individual tubes grow at different speeds and can take irregular shapes (Webber & Painter 1996); these irregularities may necessitate extensive manual corrections during analysis (Castillo et al 2022). This limitation may be the main reason for the lack of general macros to quantify germination in other species; however, the results presented here may be applicable to larch (Larix) pollen, which also follows a pre-germinative pattern similar to Pseudotsuga, as well as for other members of the genus (Ho & Rouse 1970, Takaso & Owens 1994, von Aderkas et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This code was subsequently optimized to assess pollen viability in heat-stressed tomatoes (Ayenan et al 2020), and a significant correlation was found with results obtained from manual processing, indicating that the analysis can be adjusted to different species. However, image-based analysis for estimating germinability is mostly underwhelming; neither Fiji nor PlantCV, a semi-automated software designed for this purpose (Castillo et al 2022), allow full automation due to the additional complexity conferred by pollen tube growth. Notwithstanding, such software may be useful for automating evaluation in species where pollen morphology during germination follows a more uniform or predictable pattern.…”
mentioning
confidence: 99%
“…To screen a suitable initial medium formulation for in vitro sweetpotato pollen germination, extensive pre-experiments were conducted using many pollen germination media used in other plants. We screened 10 media used in different plants [ 40 49 ] (Table 1 , M1–M10) and simplified the composition of M1 (Table 1 , M11), which had the best germination efficiency in the pre-experiments. Pollen germination rates were compared between different media and pure water (Table 1 , CK), and the medium with the highest germination rate was selected for optimisation as the initial medium for in vitro sweetpotato pollen germination.…”
Section: Methodsmentioning
confidence: 99%
“…PlantCV Version 2.1 is a Python-based package comprised of modular functions, which has remarkable flexibility, usability, and functionality in processing images from multiple platforms including red, green, and blue (RGB), Near-infrared (NIR), PSII fluorescence, thermal, and hyperspectral sensors. PlantCV has found application in the phenotypic characterization of a diversity of plant species including pennycress, Arabidopsis , wheat, teff, rice, common bean, quinoa, and more ( Castillo et al., 2022 ; Knapp et al., 2022 ; Griffiths et al., 2023 ; Pierz et al., 2023 ), underscoring its significance as a valuable tool for quantitative classification of plant phenotypes.…”
Section: Introductionmentioning
confidence: 99%